Smartness and Italian Cities. A Cluster Analysis - Boscacci, Flavio; Maltese, Ila; Mariotti, Ilaria (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Smart cities have been recently recognized as the most pleasing and attractive places to live in; due to this, both scholars and policy-makers pay close attention to this topic. Specifically, urban “smartness” has been identified by plenty of characteristics that can be grouped into six dimensions (Giffinger et al. 2007): smart Economy (competitiveness), smart People (social and human capital), smart Governance (participation), smart Mobility (both ICTs and transport), smart Environment (natural resources), and smart Living (quality of life). According to this analytical framework, in the present paper the relation between urban attractiveness and the “smart” characteristics has been investigated in the 103 Italian NUTS3 province capitals in the year 2011. To this aim, a descriptive statistics has been followed by a regression analysis (OLS), where the dependent variable measuring the urban attractiveness has been proxied by housing market prices. Besides, a Cluster Analysis (CA) has been developed in order to find differences and commonalities among the province capitals. The OLS results indicate that living, people and economy are the key drivers for achieving a better urban attractiveness. Environment, instead, keeps on playing a minor role. Besides, the CA groups the province capitals a